Overall Survival and Clinical Characteristics of BRCA‐Associated Cholangiocarcinoma: A Multicenter Retrospective Study. (July 2017) - Golan, Talia; Raitses‐Gurevich, Maria; Kelley, Robin K.; Bocobo, Andrea G.; Borgida, Ayelet; Shroff, Rachna T.; Holter, Spring; Gallinger, Steven; Ahn, Daniel H.; Aderka, Dan; Apurva, Jain; Bekaii‐Saab, Tanois; et al.
Abstract: Background: Biliary tract malignancies, in particular cholangiocarcinomas (CCA), are rare tumors that carry a poor prognosis. BRCA2 mutation carriers have an increased risk of developing CCA with a reported relative risk of ∼5 according to the Breast Cancer Linkage Consortium. In addition to this risk, there are potential therapeutic implications in those harboring somatic and/or germline (GL) BRCA mutations. Therefore, it is important to define the clinical characteristics of GL/somatic BRCA1/2 variants in CCA patients. Materials and Methods: We performed a multicenter retrospective analysis of CCA patients diagnosed between January 2000 and December 2013 with GL or somatic variants in BRCA1/2 genes detected by GL mutations testing and/or by tumor next generation sequencing. Cases were identified from clinical databases at participating institutions. Data including demographics, clinical history, surgical procedures, and systemic chemotherapy or radiation were extracted from patients' records. Results: Overall, 18 cases were identified: 5 carriers of GL BRCA1/2 mutations (4 BRCA2 ; 1 BRCA1 ) and 13 harboring somatic variations (7 BRCA1 ; 6 BRCA2 ). Mean age at diagnosis was 60, SD ± 10 years (range 36–75 years), with male and female prevalence rates of 61.2% and 38.8%, respectively. Stage at diagnosis was I ( n = 4), II ( n = 3), III ( n = 3), and IV ( n = 8). Six patients had extrahepatic CCA and the rest intrahepatic CCA. Thirteen patients received platinum‐based therapy and four were treated with poly ADP ribose polymerase inhibitors, of whom one experienced sustained disease response with a progression‐free survival of 42.6 months. Median overall survival from diagnosis for patients with stage I/II in this study was 40.3 months (95% confidence interval [CI], 6.73–108.15) and with stages III/IV was 25 months (95% CI, 15.23–40.57). Conclusion: BRCA‐associated CCA is uncommon. This multicenter retrospective study provides a thorough clinical analysis of a BRCA‐associated CCA cohort, which can serve as a benchmark for future development and design of expanded analyses and clinical trials. Implications for Practice: BRCA‐associated CCA is uncommon but a very important subtype of hepatic malignancies, due to its rising prevalence. Better clinical characterization of this subtype might allow application of targeted therapy for CCA patients with germline or somatic mutations in BRCA1/2 genes, especially due to previously reported success of such therapies in other BRCA‐associated malignancies. Thus this study, first of its kind, provides a basis for future multi‐centered analyses in larger cohorts, as well as clinical trials. Additionally, this study emphasizes the importance of both germline and somatic genotyping for all CCA patients. Abstract : It is unknown if and to what extent the clinical course and therapeutic response of BRCA‐associated cholangiocarcinomas are distinct from non‐BRCA carriers. To gain insight, this multicenter retrospective study on BRCA‐associated cases was initiated and is reported here.